The logic of desire : Aquinas on emotion - Lombardo, Nicholas E. (Nicholas Emerson) (Catholic University of America Press, 2011)
When Thomas Aquinas Completed His Treatise on the Passions, it probably constituted the longest sustained discussion of the emotions ever written. His influence on medieval and early modern philosophy was enormous, overshadowing every other medieval author on the topic of emotion. Nonetheless, Aquinas's account of emotion remains neglected by contemporary philosophers and theologians.